PENGARUH KEAHLIAN, INDEPENDENSI, DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT (Studi Empris pada Aparat Inspektorat Kabupaten Kuantan Singingi) - muslim muslim; rina andriani; zul Ammar (JURNAL EKONOMI AL-KHITMAH, 2019)
This study aimed to analyze the effect of skill, independence, and auditor ethics on audit quality in Kuantan Singingi District Inspectorate Apparatus. The population used in this study is are all Civil Servants (PNS) who work in the Kuantan Singingi District Government Inspectorate. The sampling method used in this research is by census. The data of the research were obtained from the questionnaire (primary). This study uses a type of quantitative approach and uses a type of causality. The analysis used is multiple linear regression analysis with t test and coefficient of determination. Partially result of research that is skill has a significant effect on audit quality,this result is proven with the significant value which is less than 5% (0,049<0,05), While ethic has no significant effect on audit quality, this result is proven with the significant value which is greater than 5% (0.001 <0.05), While ethic has no significant effect on audit quality, this result is proven with the significant value which is greater than 5% (0,108>0,05). Based on determination coefficient analysis (R2), 44,7% variable of audit quality were influenced by Expertise, Independence and Ethics variable, and the rest 55.3% were influenced by other factors not examined in this study.